Proteomic Landscape of Aldosterone-Producing Adenoma. Issue 2 (February 2019) - Swierczynska, Marta M.; Betz, Matthias J.; Colombi, Marco; Dazert, Eva; Jenö, Paul; Moes, Suzette; Pfaff, Cécile; Glatz, Katharina; Reincke, Martin; Beuschlein, Felix; Donath, Marc Y.; Hall, Michael N.
Abstract : Primary aldosteronism is a disease of excessive production of adrenal steroid hormones and the most common cause of endocrine hypertension. Primary aldosteronism results mainly from bilateral adrenal hyperplasia or unilateral aldosterone-producing adenoma (APA). Primary aldosteronism cause at the molecular level is incompletely understood and a targeted treatment preventing excessive adrenal steroid production is not available. Here, we perform deep quantitative proteomic and phosphoproteomic profiling of 6 pairs of APA and adjacent nontumoral adrenal cortex. We show that increased steroidogenesis in APA is accompanied by upregulation of steroidogenic enzymes (HSD3B2, CYP21A2, CYP11B2) and of proteins involved in cholesterol uptake (LSR). We demonstrate that HSD3B2 is phosphorylated at Ser95 or 96 and identify a novel phosphorylation site, Ser489, in CYP21A2, suggesting that steroidogenic enzymes are regulated by phosphorylation. Our analysis also reveals altered ECM (extracellular matrix) composition in APA that affects ECM-cell surface interactions and actin cytoskeleton rearrangements. We show that RHOC, a GTPase controlling actin organization in response to extracellular stimuli, is upregulated in APA and promotes expression of the aldosterone synthase gene CYP11B2 . Our data also indicate deregulation of protein N-glycosylation and GABAergic signaling in APAs. Finally, we find that mTORC1 (mammalian target of rapamycin complex 1) signaling is the major pathway deregulated in APA. Our study provides a rich resource for future research on the molecular mechanisms of primary aldosteronism. Abstract : Supplemental Digital Content is available in the text.